Performance of various aggregate gradings in wearing course / Taquddin Azmy Zawawi - Zawawi, Taquddin Azmy (1998)
The aggregate required in a road construction for a given pavement layer depends very much upon the form of construction which will be used. In common practice, aggregates are to be sorted beforehand into a number of closely graded 'single size' which may be subsequently remixed in desired portions in order to meet the gradation specified for used. The design of a mechanically - stable pavement involves testing of trial batches to ensure the required stability quality. In this particular project, the Marshall method of testing has been selected to determine the characteristic and performance of various aggregate gradings in wearing course. A standard aggregate grading from a standard agency has been chosen as an initial guideline in producing various aggregate gradings to be tested. Five different aggregate gradings were experimented in deducing the properties and characteristics performance of designed mix. A few determinations have been obtained. The results obtained from the testings, have shown that the aggregate gradings which consist of more coarser size aggregate is more stable then the aggregate gradings which consist of more finer size of aggregate, and the different in aggregate gradings will have a different in optimum binder content.